An Immunopharmacoinformatics Approach in Development of Vaccine and Drug Candidates for West Nile Virus - Hossain, Mohammad Uzzal; Keya, Chaman Ara; Das, Keshob Chandra; Hashem, Abu; Omar, Taimur Md.; Khan, Md. Arif; Rakib-Uz-Zaman, S. M.; Salimullah, Md. (Frontiers in Chemistry, 2018)
An outbreak of West Nile Virus (WNV) like the recent Ebola can be more epidemic and fatal to public health throughout the world. WNV possesses utmost threat as no vaccine or drug is currently available for its treatment except mosquito control. The current study applied the combined approach of immunoinformatics and pharmacoinformatics to design potential epitope-based vaccines and drug candidates against WNV. By analyzing the whole proteome of 2994 proteins, the WNV envelope glycoprotein was selected as a therapeutic target based on its highest antigenicity. After proper assessment ‘KSFLVHREW’ and ‘ITPSAPSYT’ were found to be the most potential T and B-cell epitopes, respectively. Besides, we have designed and validated four novel drugs from a known WNV inhibitor, AP30451 by adopting computational approaches. Toxicity assessment and drug score confirmed the effectiveness of these drug candidates. The effectiveness of these drug candidates was confirmed by their drug score and toxicity analysis. This in silico research might greatly facilitate the wet lab experiments to develop vaccine and drug against WNV.